The civic engagement community participation thriving model: A multi-faceted thriving model to promote socially excluded young adult women - Sagiv, Irit Birger; Goldner, Limor; Carmel, Yifat (Frontiers in Psychology, 2022)
Social policies to promote socially excluded young adult women generally concentrate on education, employment, and residence but tend to neglect thriving. The current article puts forward a Civic Engagement Community Participation Thriving Model (CECP-TM) that views thriving as a social policy goal in and of itself. It posits that civic engagement, beyond its contribution to social justice, serves as a vehicle for thriving through self-exploration and identity formation. Both are considered key components of successful maturation and thriving. Nonetheless, civic engagement and self-exploration tend not to be nurtured in socially excluded young adult women, a unique group experiencing intersecting discrimination. The model shows how active civic engagement in the context of a community of peers contributes to developing a sense of belonging and connectedness and promotes new self-reflection, identity formation, and agency capabilities. When situated within the context of intersectionality, these encourage the development of critical consciousness and new understandings of “who I am and how I fit into the social world in which we live.” These can provide a sense of meaning, contribute to identity formation, and promote the thriving of the self and the community. Several examples illustrate the model.